Primary Hydatid Cyst of Lumbar Paravertebral Muscle - Selahi, Özge; Kuru Bektaşoğlu, Pınar; Somay, Adnan; Çelikoğlu, Erhan; Gürer, Bora (Asian Journal of Neurosurgery, 2022)
Hydatid cyst disease as a zoonosis usually infests the liver and lungs, and it rarely affects muscles. Here, we presented a 36-year-old female patient with low back pain. Radiological evaluation revealed a soft tissue lesion located at the left paravertebral region without vertebral invasion. Surgical exploration and removal of the cyst were performed. The pathological diagnosis was hydatid cyst. After the surgery, the patient was treated with albendazole which is used to decrease the consequences of spillage and the possibility of recurrence. Hydatid cyst disease is rarely seen in paravertebral muscle tissue and needs to be correctly managed. Primary muscle involvement of hydatid cyst must be kept in mind for differential diagnosis of paravertebral cystic mass lesions.
Keywords: Hydatid cyst; paravertebral muscle; surgical removal